A practical approach to monitoring recovery: Development of a perceived recovery status scale - Laurent, C. M.; Green, J. M.; Bishop, P. A.; Sjökvist, J.; Schumacker, R. E.; Richardson, M. T.; Curtner-Smith, M. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to develop and test the practical utility of a perceived recovery status (PRS) scale. Sixteen volunteers (8 men, 8 women) performed 4 bouts of high-intensity intermittent sprint exercise. After completion of the baseline trial, in a repeated-measures design, subjects were given variable counterbalanced recovery periods of 24, 48, and 72 hours whereupon they repeated an identical intermittent exercise protocol. After a warm-up period, but before beginning each subsequent bout of intermittent sprinting, each individual provided their perceived level of recovery with a newly developed PRS scale. Similar to perceived exertion during exercise, PRS was based on subjective feelings. The utility of the PRS scale was assessed by measuring the level of agreement of an individual's perceived recovery relative to their performance during the exercise bout. Perceived recovery status and change (both positive and negative) in sprint performance during multiple bouts of repeated sprint exercise were moderately negative correlated (r = -0.63). Additionally, subjects were able to accurately assess level of recovery using the PRS scale indicated by correspondence with negative and positive changes in total sprint time relative to their previous session. The ability to detect changes in performance using a noninvasive psychobiological tool to identify differences in performance was independent of other psychological and physiological markers measured during testing, because there were no differences (p > 0.05) among ratings of perceived exertion (RPE), heart rate, blood lactate concentration, or session RPE values among any of the performance trials. Although further study is needed, current results indicate a subjective approach may be an effective means for assessing recovery from day to day, at least under similar conditions.